Gender equity and the sustainability of farming improved vegetable varieties: an analysis of tomato and African eggplant production in southern Mali - Fischer, G.; Cavicchioli, M.; Traore, A.S.; Tignegre, J.B.; Jimah, K.; Wittich, S.; Badolo, F.; Dicko, M.; Diallo, C. (2025)
Despite its low integration into breeding programs in Africa, vegetable cultivation is increasingly seen as contributing to the achievement of several Sustainable Development Goals, including gender equality and women’s empowerment. Seeking evidence of this, we analyze a genetic intensification activity offering improved tomato and African eggplant varieties to women and men farmers in southern Mali. We use a sustainable intensification assessment framework (SIAF), with a mixed methods approach, to conduct a gender analysis of this activity in five sustainability domains. Results and recommendations underline that breeding initiatives need to be accompanied by measures that transform the gender relations in which production is embedded. Equity emerges as a precondition for sustainable vegetable farming.